ANALISIS EKSPOR IKAN TUNA INDONESIA - Indriana - Yudiarosa (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT Facing the free trade era, Indonesia needs to reorganize its export strategies with not mainly depending on oil and gas sector only. In relation to this, tuna as Indonesia’s export commodity has plate an important role but presently Indonesia can only contribute 7% of the world tuna supply. Being one of the country which have unused tunas potensial up to 53,7%, Indonesia’s opportunity to supply world market is the large. This studied was aimed at analyzing; factors influencing Indonesia’s tunas export; factors influencing domestic supply of tunas; predicting tunas export in the next 5 years (2000 –2005) and study marketing strategies that effect Indonesia’s export of tuna. To analyze factors that influenced tunas export and domestic supply of tunas, simultan equation in the form of double logarithma with two stage least square (2SLS) methods were used. Meanwhile, export development were analyzed with trend analysis and tunas export strategies with SWOT analysis. Result of this study showed that, tunas export price, tunas export tax, exchange rate and tunas export the previous year effected tunas export.Factors that influenced domestic tuna supplies were domestic prices of tunas and domestic supplies of tunas the previous year. Tunas export prediction from 2000 – 2005 drawn from the trend analysis; shows an increase in export by average of 1.06%. Hopefully this will be followed by increase in tunas production by an average of 1.27%. Increase in tunas export must be supported by marketing strategies.Marketing strategies that can be carried out based on the SWOT analysis are improving infrastucture, transfer of technology for fleet and catch material, improvement in the quality and quantity of the product , marketing research and upgrading cooperation with importing countries. Keywords: tuna fish, export